2022
DOI: 10.1016/j.jhsg.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Measured Cross-Sectional Area of the Median Nerve

Abstract: The size of the median nerve may serve as a useful parameter to predict carpal tunnel syndrome (CTS) in a subset of patients. The purpose of this study was to evaluate magnetic resonance imagingebased measurements of median nerve cross-sectional area (CSA) to examine trends between patient subgroups and CSA that may assist in predicting the individuals who are most likely to develop CTS symptoms. Methods: A retrospective chart review of 1,273 wrist magnetic resonance images was performed, and the images were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Research has shown increasing BMI is correlated with increased median nerve cross-sectional area. 23 Our studies show patients with lower BMI are more likely to have signs and symptoms of carpal tunnel without increases in median nerve cross-sectional area reaching diagnostic thresholds. Therefore, patients with lower BMI may be more likely to have false-negative US studies despite positive CTS-6.…”
Section: Discussionmentioning
confidence: 58%
“…Research has shown increasing BMI is correlated with increased median nerve cross-sectional area. 23 Our studies show patients with lower BMI are more likely to have signs and symptoms of carpal tunnel without increases in median nerve cross-sectional area reaching diagnostic thresholds. Therefore, patients with lower BMI may be more likely to have false-negative US studies despite positive CTS-6.…”
Section: Discussionmentioning
confidence: 58%
“…Regarding the relationships between physical characteristics and median nerve CSA, previous studies suggested a positive correlation between BMI and median nerve CSA [ 37 , 38 , 39 , 40 , 41 ]. Cartwright et al reported that mean age based on BMI was a major parameter for predicting median nerve CSA in healthy subjects [ 42 ]. Other studies demonstrated that BMI and diabetes were associated with larger median nerves at the CT [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that BMI and diabetes were associated with larger median nerves at the CT [ 39 , 40 , 41 ]. An MRI-based median nerve CSA study also showed that CSA increased with BMI in non-CTS patients, and obese patients with CTS had larger CSA values at the CT inlet level [ 42 ]. The mechanism by which obesity/high BMI increases median nerve CSA is unknown.…”
Section: Discussionmentioning
confidence: 99%